Magnetic Pulsation Conjugacy and Its Mechanisms - Lanzerotti, L.J. (1974)
P(論文) A brief review and discussion is given of an investigation of the characteristics of the naturally-occurring ULF plasma waves in the magnetosphere near L=4. The investigation was carried out using similarly-instrumented magnetometer stations at Siple, Antarctica and in the conjugate region at Lac Rebours, Quebec. The waves were predominantly in the Pc-3 frequency range. No magnetospheric waves that satisfied an imposed strict selection criterion were observed after ∿1700 LT. Approximately half of the 94 accepted events were left-hand elliptically polarized, with no significant change in polarization characteristics observed as a function of local time. However, a distinct preferential orientation direction as a function of local time was observed for the major axes of the polarization ellipses. Approximately 16% of the events had opposite polarizations in the two hemispheres; this may be a manifestation of occasional station non-conjugacy combined with a narrow (in latitude) extent of wave localization. All but two of the events were symmetrical about the meridian plane, implying an odd-mode standing oscillation of the geomagnetic field lines. A significant local time dependence observed in the relative orientations of the plane of the Pc-3 waves is interpreted as a possible effect of the ionosphere on the transmission of the ULF waves. departmental bulletin paper